The Cambridge history of religions in the ancient world - Salzman, Michele R.; Sweeney, Marvin A.; Adler, William (Cambridge University Press, 2013)
The Cambridge History of Religions in the Ancient World provides a comprehensive examination of the history of the religions of the ancient Near East and Mediterranean world. The essays in these volumes have a broad reach, covering the ancient Near East and Mediterranean, and extending from the Bronze Age into the late Roman period. Its contributors, acknowledged experts in their fields, incorporate a wide spectrum of textual and material evidence into their analyses of their fields. The regional and historical orientations of the essays will enable readers to see how a religious tradition or movement assumed a distinctive local identity, as well as to understand how each tradition developed within its broader regional context. Supplemented with maps, illustrations and detailed indexes, these volumes will be an excellent reference tool for scholars and students